(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article examines the effective integration of technologies into pedagogical practice, presenting them as a vital part of modern education. Tools like Google Classroom and Kahoot contribute to an interactive and enjoyable learning environment, while AR/VR technologies offer an immersive experience. It also highlights the importance of online collaboration platforms like Google Docs for developing critical 21st-century skills. However, challenges such as the digital divide and the need for continuous teacher training are recognized. The article concludes that technology should complement traditional teaching methods, striking a balance between digital tools and human interaction for effective learning.